Abnormal uterine bleeding in peri and post menopausal women: comparison of efficacy of saline infusion sonography with transvaginal sonography - Pal, Richa; Naik, Balakrishna; Puttanna, V. N. (International Journal of Research in Medical Sciences, 2022)
Background: Abnormal uterine bleeding (AUB) can present with menorrhagia or metrorrhagia but cannot indicate the cause of the bleeding, so further investigation is always needed. This study aimed to assess the role of Saline infusion sonography (SIS) in evaluating the intracavitary uterine lesions in comparison to transvaginal ultrasound (TVS) and thereby short listing the patients for hysteroscopy. Methods: This prospective analytical study was conducted in 64 women presenting with AUB in OBG department, Mazumdar Shaw Medical Center, Bangalore from November 2014 to November 2015. Transvaginal ultrasound, followed by SIS were performed for all. Hysterectomy specimen (gross cut section and histopathology) taken as gold standard. Findings at TVS and SIS were compared with gold standard. Results: Findings were analysed by Chi-square test. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of SIS and TVS in detecting intracavitary abnormalities were calculated. SIS found to be more sensitive and specific when compared to TVS. Discrepancies in detection of polyp seen. 13 cases of polyp were missed in TVS, indicating high false negative rate of TVS, whereas no polyps were missed by SIS. In our present study, ET (endometrial thickness) of more than 18 mm was observed in TVS in 6 cases and all these cases turned out to be polyp in SIS, indicating need of SIS or hysteroscopy whenever ET is more than 18 mm in TVS. Conclusions: Study results have substantiated that SIS is a better tool as compared to TVS for the assessment of uterine intra-cavitary lesions especially polyps.